Handbook of Remote Biometrics for Surveillance and Security - Tistarelli, Massimo; Li, Stan Z.; Chellappa, Rama (Advances in Computer Vision and Pattern Recognition, 2009)
The study of biometrics aims to understand the uniqueness of human physical characteristics, and to develop biometric identification technologies. Remote biometrics address the most challenging problem of biometrics, that of identifying individuals in a watch list from a distance. From a computing point of view, this is a complex task requiring four issues to be solved. First, the system must be able to recognize individual subjects with minimum errors. Second, this must be able to operate at a distance of up to 50 meters. Third, it must be able to deal with subjects in motion. Finally, the system must function when the subjects are unaware of being observed. Other issues include allowing countermeasures to be made against attacks or providing intelligence for security intervention. No currently commercial system is able to satisfy all of these requirements, and none are error-free. This comprehensive and innovative handbook covers several aspects of biometrics from the perspective of recognizing individuals at a distance, in motion, and under a surveillance scenario. The book presents both a broad coverage and an in-depth investigation into the most advanced biometric technologies for recognition at a distance, with applications in areas such as border control, surveillance in critical infrastructures, and ambient intelligence. Features: • Starts with a thorough introductory chapter • Provides topics from a range of different perspectives offered by an international collection of leading researchers in the field • Contains selected expanded contributions from the 5th IAPR International Summer School for Advanced Studies on Biometrics for Secure Authentication • Investigates issues of iris recognition, gait recognition, and touchless fingerprint recognition, as well as various aspects of face recognition • Discusses multibiometric systems, and machine learning techniques • Examines biometrics ethics and policy • Presents international standards in biometrics, including those under preparation This state-of-the-art volume is designed to help form and inform professionals, young researchers, and graduate students in advanced biometric technologies. This indispensible reference draws from the expertise of internationally regarded experts in the field, as well as from the finest presentations of the 5th International Summer School on Biometrics. Dr. Massimo Tistarelli is Professor of Computer Science at the Department of Architecture and Planning at the University of Sassari, Italy. Dr. Stan Z. Li is Professor of the Chinese Academy of Sciences and the Director of the Center for Biometrics and Security Research, at the Institute of Automation, Beijing, China. Dr. Rama Chellappa is the Minta Martin Professor of Engineering and Director of the Center for Automation Research at the University of Maryland, USA. Key topics: • Iris Recognition at a Distance • Gait Recognition • Touchless Fingerprint Recognition • Face Recognition at a Distance • Multibiometric Systems • Biometrics Ethics and Policy.